Fungsi Agama Dalam Perspektif Umat Islam di Indonesia - Muhammad Farhan Fadhilah; Muhammad Ihsan Nauval Musyari; Muhammad Badil; Rivaldi Rissyel (Pusat Riset dan Inovasi Nasional, 2024)
The role of religion in the lives of individuals to function as a value system that includes certain norms. Religion influential as motivation in encouraging individuals to perform an activity, due to actions undertaken against a background of religious beliefs assessed as having elements of chastity, and obedience. Religion in the lives of individuals also serves as 1) .Sumber Value In Keeping Decency 2). As Means To Overcome Frustration, 3). As Means To Satisfy Curiosity. Furthermore, with regard to the function of religion in public life. Society is the union of a group of individuals formed by a certain social order. The issue of religion would never be able to be separated from public life, because religion itself turned out to be necessary in social life. In practice, the function of religion in society, among others: 1). Educational function, 2). Rescuer, 3) As of Atonement, 4). As Social Control, 5). As fertilizer Sense of Solidarity. 6). Transformative function, 7). Creative function, 8). Sublimatif function, and 9). Sublimatif function. For further relates to the prosperity and happiness of human beings according to the teachings of Islam can be seen from all sides of which are 1) Social Kewajiban Human, 2). Humans as Pemakmur, and 3). Life Strategies as a winner.